Influence of Urban Renewal on the Assessment of Housing Market in the Context of Smart City Development - Rącka, I.; Palicki, S. (EAI Endorsed Transactions on Smart Cities, 2016)
The variability of the urban environment, where the symptoms are observed in terms of spatial, aesthetic, architectural, urban and socio-economic development, seems to be relevant to the functioning of the local real estate market. Housing issue is the vital component of sustainable socioeconomic city development. The perception of the property attractiveness is determined by price-setting attributes such as: building standard, area, utilities, zoning and also location and neighbourhood. The attractiveness of the residential property is manifested in its market value. As part of the follow-urban transformation, it seems to be important to reconstruct the impact of the neighbourhood changes on the housing market. The authors attempt to explain the ensuing problem on the example of one of the streets in a Polish city – Kalisz, which over the years has gained a new streetscape and market image. They endeavour to simulate changes in the market value of selected properties located on the street, in order to map the influence of changes on the value.